STUDI PENDAHULUAN PENGEMBANGAN MEDIA FLIPBOOK BERBASIS AJARAN TRI-NGA DALAM MENINGKATKAN KEGIATAN LITERASI NUMERASI SD - Budi Artopo; Siti Rochmiyati; Banun Havifah Cahyo Khosiyono (Tuladha : Jurnal Pendidikan Dasar, 2023)
In order for the learning process to be successful and run well, the teacher must have the right initiatives and steps in terms of encouraging students to be active in learning and providing adequate learning experiences to students. One of the efforts that can be made in the field of education is through the use of learning resources, books and Student Worksheets, which are converted into digital learning resources that are more attractive, interactive and cost-effective without reducing their functions, benefits and uses. Numerical literacy is knowledge and skills in using numbers and symbols related to basic mathematics to solve contextual problems and analyze information presented in various forms, then interpret the results of the analysis to predict and make decisions. Research and development data analysis uses qualitative data which requires a different analysis to interpret the data that has been collected. The development of Flipbook media based on tri-nga teachings can increase elementary school numeracy literacy activities with significant results.